Answer:
3 one
Step-by-step explanation:
Solve using trigonometry
tan(39)=24/b
b=24/tan(39)
so b=29.6
for c…
sin(39)=24/c
c=24/sin(39)
c=38.1
The question is not well-expressed, but it looks like you want to evaluate
5 + (-3) - 65 + (-3) - 65 + (-3) - 6
Answer:
-140
Step-by-step explanation:
First of all, note the following
- Multiplying a negative number by another negative number gives a positive number.
- Multiplying a negative number by a positive number gives a negative number.
- Multiplying a positive number by a positive number gives a positive number.
- Brackets mean multiplication.
So
5 + (-3) - 65 + (-3) - 65 + (-3) - 6
= 5 - 3 - 65 - 3 - 65 - 3 - 6
= -140